Potential therapeutic application of probiotics in the treatment of neuropathic pain: A mechanistic aspects of brain-gut axis - Mishra, Manshi; Subhan, Abdus; Mishra, Riddhi; Mazumder, Avijit; Kumar, Bimlesh; Joshi, Kardam (Trends in Immunotherapy, 2023)
The “gut-brain axis” or “brain-gut axis” communication mechanism has a bidirectional approach because it depends on showing top-down or bottom-up channels to function. It is one of the few systems in the body that combines neuronal routes with humoral pathways, which include cytokines, hormones, and neuropeptides as chemical messages. It was also discovered to be diverse because it contains spinal, vagus, sympathetic, and intestinal nerves. The role of microbes as signaling agents in the gut-brain axis has been proven by the most recent research, which is primarily based on animal models. Probiotics are living bacteria that improve one’s health when ingested in large enough doses. Gut microbes are suspected to play a role in a variety of psychiatric disorders, making them a potential therapeutic target. The stomach and the brain are linked via a two-way communication pathway called the microbiota-gut-brain axis. Current interventional research on probiotics and the gut-brain axis has been evaluated for its findings in the treatment of depression, anxiety, and schizophrenia. Neuropathic pain is brought on by a lesion or injury to the nerve system, which is further demonstrated by a malfunction of the somatosensory system. Such a developed form of pain affects both peripheral and central nervous system neurons. According to research, probiotics can enhance the gut’s dynamic environment and are good for both the gut and the brain. Therefore, the focus of this review is on how probiotics, the microbiota-gut-brain axis, and the gut-brain axis relate to neuropathic pain.